On the Effect of Wall Slip on the Determination of the Yield Stress of Magnetorheological Fluids - Caballero-Hernandez Jaime; Gomez-Ramirez Ana; Duran Juan D.G.; Gonzalez-Caballero F.; Zubarev Andrey Yu.; Lopez-Lopez Modesto T. (Applied Rheology, 2017)
We study the effect of wall slip on the measured values of the yield stress of magnetorheological (MR) fluids. For this aim we used a rheometer provided with parallel-plate geometries of two types, distinguished by having smooth or rough surfaces. We found that wall slip led to the underestimation of the yield stress when measuring geometries with smooth surfaces were used, and that this underestimation was more pronounced for the static than for the dynamic yield stress. Furthermore, we analysed the effect that both irreversible particle aggregation due to colloidal interactions and reversible magnetic fieldinduced particle aggregation had on the underestimation provoked by wall slip. We found that the higher the degree of aggregation the stronger the underestimation of the yield stress. At low intensity of the applied magnetic field irreversible particle aggregation was dominant and, thus, the underestimation of the yield stress was almost negligible for well-dispersed MR fluids, whereas it was rather pronounced for MR fluids suffering from irreversible aggregation. As the magnetic field was increased the underestimation of the yield stress became significant even for the best dispersed MR fluid.